GPR37 Activation Alleviates Bone Cancer Pain via the Inhibition of Osteoclastogenesis and Neuronal Hyperexcitability - Kaiyuan Wang; Yongfang Zhang; Ruichen Shu; Limei Yuan; Huifang Tu; Shengran Wang; Bo Ni; Yi‐Fan Zhang; Changyu Jiang; Yuhui Luo; Yiqing Yin (Advanced Science)
Abstract Osteolytic bone cancer pain is a primary concern for cancer patients with bone metastasis, and current therapies offer inadequate pain relief. The present study demonstrates that activation of the G protein‐coupled receptor 37 (GPR37) by neuroprotectin D1 (NPD1) or artesunate (ARU) alleviates both acute and persistent pain in multiple mouse models of bone cancer. GPR37 agonists also protect against cancer‐induced bone destruction. Mechanistically, NPD1 or ARU binding to GPR37 in macrophages promotes the release of IL‐10, which further inhibits cancer‐induced osteoclastogenesis. Moreover, direct activation of GPR37 in dorsal root ganglion (DRG) neurons and the spinal dorsal horn reduces action potential firing and the frequency of spontaneous excitatory postsynaptic currents (sEPSCs), thereby suppressing cancer‐induced neuronal hyperexcitability. Importantly, the analgesic and protective effects of NPD1 and ARU are abolished in Gpr37−/− mice, and β‐arrestin 2 is identified as a key mediator in IL‐10 release and neuronal inhibition. In patients with bone metastases, plasma levels of endogenous NPD1 are negatively correlated with both pain intensity and the bone resorption marker CTX‐I. Collectively, these findings highlight GPR37 activation as a potential therapeutic strategy for alleviating bone cancer pain through direct and synergistic inhibition of osteoclastogenesis and neuronal hyperexcitability.